"Tau immunotherapy: Hopes and hindrances". Issue 2 (1st February 2018) - Shahpasand, Koorosh; Sepehri Shamloo, Alireza; Nabavi, Seyed Massood; Ping Lu, Kun; Zhen Zhou, Xiao
ABSTRACT: Alzheimer's disease (AD) is a progressive neurological disorder having two major pathological hallmarks: the extracellular senile plaques and intracellular neurofibrillary tangles composed of amyloid beta protein and hyperphosphorylated tau respectively. Removal of protein deposits from AD brains are the newer attempts for treating AD. The major developments in this direction have been the amyloid and tau based therapeutics. While senile plaque removal employing monoclonal antibodies (mAbs) restore brain function in mouse models of AD, tau has been recently introduced as the major neurodegenerative factor mediating neural cell death. So, several research groups have focused on tau therapy. So far, the outcome of tau immunotherapy has been promising and clearance of hyperphosphorylated tau has been shown to restore the brain function in animal models. But the point is which phosphorylated tau is the most critical form to be removed from the brain, especially because removal of physiologic tau can cause neurodegenerative consequence. Recently, we have shown that phosphorylated tau at Thr231 in the cis conformation is a very early driver of neurodegeneration and cis mAb treatment efficiently restores brain structure and function in TBI models. Because of efficient therapeutic effects in mice model of TBI and considering cis pT231-tau accumulation in AD brains, it could be a very good candidate for tau immunotherapy upon several tauopathy disorders including AD.